Evaluation of needs and supply of emergency care in Kinshasa, Democratic Republic of Congo: a cross-sectional household survey. Issue 7 (12th July 2022) - Diango, Ken; Yangongo, John; Sistenich, Vera; Hodkinson, Peter; Mafuta, Eric; Wallis, Lee
Abstract : Objective: Emergency care can address over half of deaths occurring each year in low-income countries. A baseline evaluation of the specific needs and gaps in the supply of emergency care at community level could help tailor suitable interventions in such settings. This study evaluates access to, utilisation of, and barriers to emergency care in the city of Kinshasa, Democratic Republic of Congo. Design: A cross-sectional, community-based household survey. Setting: 12 health zones in Kinshasa, Democratic Republic of Congo. Participants: Three-stage randomised cluster sampling was used to identify approximately 100 households in each of the 12 clusters, for a total of 1217 households. The head of each household or an adult representative responded on behalf of the household. Additional 303 respondents randomly selected in the households were interviewed regarding their personal reasons for not accessing emergency care. Primary outcome: Availability and utilisation of emergency care services. Results: In August 2021, 1217 households encompassing 6560 individuals were surveyed (response rate of 96.2%). Most households were economically disadvantaged (70.0% lived with <US100 per person per month) and had no health insurance (98.4%) in a country using a fee-for-service healthcare payment system. An emergency visit in the last 12 months was reported in 52.6% of households. Ambulance utilisation was almost non-existent (0.2%) and access to health facilities for emergencies was mostly by walking (60.6% and 56.7% by day and night, respectively). Death in the last 12 months was reported in 12.8% of households, of which 20.6% occurred out-of-hospital with no care received within 24 hours prior to death. Self-medication (71.3%) and the expected high cost of care (19.5%) were the main reasons for unmet emergency care needs. Conclusion: There is a substantial gap in the supply of emergency care in Kinshasa, with several unmet needs and reasons for poor access identified.